Diaphragmatic plication for iatrogenic respiratory insufficiency after cardiothoracic surgery - Uchida, Takahiro (J Thorac Dis, 2019)
BACKGROUND: The efficacy of diaphragmatic plication (DP) has been proven in many studies. However, there are few reports on DP for patients with severe respiratory conditions requiring mechanical ventilation. The study aim was to demonstrate the efficacy of DP for patients with severe respiratory insufficiency after cardiothoracic surgeries. METHODS: We retrospectively reviewed 10 patients who underwent DP for severe respiratory insufficiency due to postoperative diaphragmatic paralysis; eight of them required mechanical ventilation, and two needed high-flow oxygen therapy prior to DP. The symptoms, lung function, and elevation of the diaphragm were assessed before and after DP. RESULTS: All patients were successfully withdrawn from mechanical ventilation after DP and discharged without the need for oxygen therapy. The mean perioperative Medical Research Council (MRC) dyspnea scale (ATS/ERS 2004) score improved in 30 days (from 4 to 1.8) and in 90 days (from 4 to 0.6) after DP. Lung dynamic compliance was also ameliorated (mean improvement: 41.9 to 60.7 mL/cmH2O). Radiography revealed improved elevation of the diaphragm (mean improvement of 1.8 intercostal spaces, range, 1–2). Mean hospital stay after DP was 65.5 days (range, 25–187 days). One patient who underwent DP with endostapler-only suturing required re-operation because of staple line ruptures. CONCLUSIONS: DP was found to be an effective form of treatment for patients with severe respiratory insufficiency after cardiothoracic surgery.